A zebrafish larval model reveals early tissue-specific innate immune responses to Mucor circinelloides - Kerstin Voelz; Remi L. Gratacap; Robert T. Wheeler (The Company of Biologists, 2015)
Mucormycosis is an emerging fungal infection that is clinically difficult to manage, with increasing incidence and extremely high mortality rates. Individuals with diabetes, suppressed immunity or traumatic injury are at increased risk of developing disease. These individuals often present with defects in phagocytic effector cell function. Research using mammalian models and phagocytic effector cell lines has attempted to decipher the importance of the innate immune system in host defence against mucormycosis. However, these model systems have not been satisfactory for direct analysis of the interaction between innate immune effector cells and infectious sporangiospores in vivo. Here, we report the first real-time in vivo analysis of the early innate immune response to mucormycete infection using a whole-animal zebrafish larval model system. We identified differential host susceptibility, dependent on the site of infection (hindbrain ventricle and swim bladder), as well as differential functions of the two major phagocyte effector cell types in response to viable and non-viable spores. Larval susceptibility to mucormycete spore infection was increased upon immunosuppressant treatment. We showed for the first time that macrophages and neutrophils were readily recruited in vivo to the site of infection in an intact host and that spore phagocytosis can be observed in real-time in vivo. While exploring innate immune effector recruitment dynamics, we discovered the formation of phagocyte clusters in response to fungal spores that potentially play a role in fungal spore dissemination. Spores failed to activate pro-inflammatory gene expression by 6 h post-infection in both infection models. After 24 h, induction of a pro-inflammatory response was observed only in hindbrain ventricle infections. Only a weak pro-inflammatory response was initiated after spore injection into the swim bladder during the same time frame. In the future, the zebrafish larva as a live whole-animal model system will contribute greatly to the study of molecular mechanisms involved in the interaction of the host innate immune system with fungal spores during mucormycosis.